RANCANGAN PLTS ATAP DI GEDUNG RUMAH JABATAN GUBERNUR PROVINSI BALI - Ayu Anggasari, Ni Luh; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p15, 2023)
Indonesia aims to achieve a 23% utilization of new renewable energy (EBT) by 2025. This form of clean and sustainable energy derives from sources such as solar, water, mini/microhydro, geothermal, and bioenergy, all of which have minimal to no environmental impact. The Provincial Government of Bali has introduced a directive to promote the adoption of EBT. The choice of the Bali Provincial Governor's Office for this initiative stems from its significant electricity consumption and its potential to serve as a model for photovoltaic solar (PLTS) development in Bali.This study delves into the conceptualization of a PLTS system installed atop the Bali Provincial Governor's residence. The design process involves determining the appropriate quantity of solar panels for the roof, evaluating the potential electrical output of the PLTS, selecting the specific PLTS model and inverter for implementation. To aid in this endeavor, the Helioscope software is employed, aiding in the visualization of the PLTS layout and its potential energy generation.Four distinct scenarios were considered in this study: In Scenario 1, a configuration employing 114 solar modules with a total capacity of 63.7 kWp is proposed, utilizing a single inverter with a capacity of 66 kW. Scenario 2 adopts a setup with 64 solar modules, yielding 35.3 kWp in capacity, coupled with a single inverter boasting 36 kW capacity. Scenario 3 envisions the installation of 142 solar modules generating 78.1 kWp, harmonized with a lone 80 kW inverter. Lastly, Scenario 4 opts for 64 solar modules producing 35.3 kWp, each equipped with 22 microinverters with a capacity of 2000 Watt.